2018 - Rebiger, Bill (Yearbook of the Maimonides Centre for Advanced Studies, 2018)
The Yearbook mirrors the annual activities of staff and visiting fellows of the Maimonides Centre and reports on symposia, workshops, and lectures taking place at the Centre. Although aimed at a wider audience, the yearbook also contains academic articles and book reviews on scepticism in Judaism and scepticism in general. Staff, visiting fellows, and other international scholars are invited to contribute.